Ambient circulation surrounding an ablation catheter tip affects ablation lesion characteristics. (8th March 2023) - Nussinovitch, Udi; Wang, Paul; Babakhanian, Meghedi; Narayan, Sanjiv M.; Viswanathan, Mohan; Badhwar, Nitish; Zheng, Lijun; Sauer, William H.; Nguyen, Duy T.
Abstract: Introduction: The association between ambient circulating environments (CEs) and ablation lesions has been largely underexplored. Methods: Viable bovine myocardium was placed in a saline bath in an ex vivo endocardial model. Radiofrequency (RF) ablation was performed using three different ablation catheters: 3.5 mm open irrigated (OI), 4, and 8 mm. Variable flow rates of surrounding bath fluids were applied to simulate standard flow, high flow, and no flow. For in vivo epicardial ablation, 24 rats underwent a single OI ablation and performed with circulating saline (30 ml/min; n  = 12), versus those immersed in saline without circulation ( n  = 12). Results: High flow reduced ablation lesion volumes for all three catheters. In no‐flow endocardial CE, both 4 mm and OI catheters produced smaller lesions compared with standard flow. However, the 8 mm catheter produced the largest lesions in a no‐flow CE. Ablation performed in an in vivo model with CE resulted in smaller lesions compared with ablation performed in a no‐flow environment. No statistically significant differences in steam pops were found among the groups. Conclusion: A higher endocardial CE flow can decrease RF effectiveness. Cardiac tissue subjected to no endocardial CE flow may also limit RF for 4 mm catheters, but not for OI catheters; these findings may have implications for RF ablation safety and efficacy, especially in the epicardial space without circulating fluid or in the endocardium under varying flow conditions. Abstract : (A) Experimental settings. (B–D) Representative ablation lesions following an ex vivo ablation with 8mm‐AC. (E, F) Boxplots showing the association between lesion volume in vitro, using 8mm‐AC (E), and in vivo, using an open‐irrigated (OI)‐AC (F). * p  < .05, ** p  < .01, *** p  < .001.